Attesting the efficiency of monitored natural attenuation in the detoxification of sewage sludge by means of genotoxic and mutagenic bioassays - Mazzeo, Dânia Elisa Christofoletti [UNESP]; Fernandes, Thaís Cristina Casimiro [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Elsevier, 2016)
A viable alternative to the use of sewage sludge (SS) would be using it as a reconditioner of agricultural soils, due to its high content of organic matter and nutrients. However, this solution may contaminate the soil, since SS may contain toxic substances. Monitored natural attenuation is a process that can be used in the decontamination of SS before its disposal into the environment. The effectiveness of the natural attenuation of a domestic SS was evaluated over 12 months by assays of Salmonella/microsome and micronucleus (MN) in human hepatoma cells (HepG2). Mutagenic activity was observed for the Salmonella strain TA 100, with S9, for the extracts from periods 0–6 months of natural attenuation. Genotoxic effects were observed in HepG2 cells, for 0 and 2 months, in almost all tested concentrations. Comparing obtained data by MN test to chemical analyses, it is possible to observe a coincidence between the induction of MN and the quantity of the m- and p-cresol, since these compounds were present in the initial SS and after 2 months of natural attenuation, decreasing their concentrations in samples from 6 to 12 months. The positive results obtained with Salmonella/microsome (from 6 months) suggest a combined action of other substances in SS. These results indicated that this SS, in the earlier periods tested, is potentially genotoxic and mutagenic and that its disposal can lead to severe environmental problems. Thus, the use of the studied SS as reconditioner requires pre-processing for over than 6 months of natural attenuation.
Keywords: HepG2 cells; In vitro test; Micronucleus; Salmonella assay; Solid waste